Advantages of using internet resources in modern teaching methods - Ismatova, Maxzuna (The Lingua Spectrum, 2025)
In today’s education system, the need to effectively organize the learning process by using new technologies and internet resources is increasingly growing. Internet resources provide not only teachers but also students with the opportunity to conduct the learning process in new forms. This article discusses the effective methods of using internet resources in the educational process.